2014
DOI: 10.2147/orr.s44747
|View full text |Cite
|
Sign up to set email alerts
|

Eluting antibiotic bone graft substitutes for the treatment of osteomyelitis in long bones. A review: evidence for their use?

Abstract: Despite continuous advances in surgical procedures and antibiotic therapies, osteomyelitis still remains one of the most devastating complications in trauma and orthopedic surgery. Treatment of osteomyelitis represents a severe and challenging problem, even if the treatment of acute cases with systemic antibiotics has good success rates. Chronic cases need a consequent resection of dead or infected bone in addition to an improved systemic and local antibiotic therapy. The gold standard therapy is the implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 81 publications
0
15
1
6
Order By: Relevance
“…Local delivery of antibiotics from degradable combination devices represents potentially promising advantages over current methods utilized to treat these infections. 9,15,17,18,20,24,30,32 A previous in vivo study evaluating the group 1 device 20 reported that this device did not degrade in situ. Furthermore, the glassy surface of the device provoked a foreign body response resulting in the fibrous encapsulation of the device.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local delivery of antibiotics from degradable combination devices represents potentially promising advantages over current methods utilized to treat these infections. 9,15,17,18,20,24,30,32 A previous in vivo study evaluating the group 1 device 20 reported that this device did not degrade in situ. Furthermore, the glassy surface of the device provoked a foreign body response resulting in the fibrous encapsulation of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of PJI following total knee arthroplasty continues to challenge clinicians despite advancements in surgical and antimicrobial techniques. Local delivery of antibiotics from degradable combination devices represents potentially promising advantages over current methods utilized to treat these infections . A previous in vivo study evaluating the group 1 device reported that this device did not degrade in situ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other desirable properties of scaffolds include osteoconduction, osteoinduction and osteogenesis [25,39,40]. Osteoconduction is the ability to guide reparative bone growth.…”
Section: Bone Growthmentioning
confidence: 99%
“…Over time, the result can be destruction of the bone itself. 1 Ciprofloxacin is a broad-spectrum fluoroquinolone antibacterial agent used in the treatment of osteomyelitis caused by pathogens like Staphylococcus aureus and Pseudomonas aeruginosa. 2 A high concentration of the drug is required for 5 weeks to several months to cure the bone infection.…”
Section: Introductionmentioning
confidence: 99%